Accurate estimation of seismic source parameters of induced seismicity by a combined approach of generalized inversion and genetic algorithm: Application to The Geysers geothermal area, California. Issue 5 (29th May 2017) - Picozzi, M.; Oth, A.; Parolai, S.; Bindi, D.; De Landro, G.; Amoroso, O.
Abstract: The accurate determination of stress drop, seismic efficiency, and how source parameters scale with earthquake size is an important issue for seismic hazard assessment of induced seismicity. We propose an improved nonparametric, data‐driven strategy suitable for monitoring induced seismicity, which combines the generalized inversion technique together with genetic algorithms. In the first step of the analysis the generalized inversion technique allows for an effective correction of waveforms for attenuation and site contributions. Then, the retrieved source spectra are inverted by a nonlinear sensitivity‐driven inversion scheme that allows accurate estimation of source parameters. We therefore investigate the earthquake source characteristics of 633 induced earthquakes ( M w 2–3.8) recorded at The Geysers geothermal field (California) by a dense seismic network (i.e., 32 stations, more than 17.000 velocity records). We find a nonself‐similar behavior, empirical source spectra that require an ω γ source model with γ > 2 to be well fit and small radiation efficiency η SW . All these findings suggest different dynamic rupture processes for smaller and larger earthquakes and that the proportion of high‐frequency energy radiation and the amount of energy required to overcome the friction or for the creation of new fractures surface changes with earthquake size. Furthermore, we observe also two distinct families of events with peculiar source parameters that in one case suggests the reactivation of deep structures linked to the regional tectonics, while in the other supports the idea of an important role of steeply dipping faults in the fluid pressure diffusion. Key Points: A novel data‐driven strategy for monitoring induced seismicity that combines generalized inversion and genetic algorithm is presented Studying the seismicity at The Geysers geothermal field, we found different dynamic rupture processes for smaller and larger earthquakes Two groups of events suggest the reactivation of deep structures and an important role of steeply dipping fault in fluid pressure diffusion